Study of Pseudostate Expansion in a Simplified Model of Elastic Electron Scattering from Helium - Agus Kartono; Toto Winata (Jurnal Matematika & Sains, 2005)
In this paper, we present a simplified model of electron-helium scattering in which all terms involving nonzero orbital angular momentum are neglected. Elastic scattering cross sections are calculated for this model by using the close-coupling expansion with a non-orthogonal Laguerre-L2 basis function. It is found that the results are in good agreement with experiments and with the other theoretical results.